Surface Oxygen Injection in Tin Disulfide Nanosheets for Efficient CO2 Electroreduction to Formate and Syngas - Chen, Tao; Liu, Tong; Ding, Tao; Pang, Beibei; Wang, Lan; Liu, Xiaokang; Shen, Xinyi; Wang, Sicong; Wu, Dan; Liu, Dong; Cao, Linlin; Luo, Qiquan; et al. (Nano-Micro Letters, 2021)
Surface chemistry modification represents a promising strategy to tailor the adsorption and activation of reaction intermediates for enhancing activity. Herein, we designed a surface oxygen-injection strategy to tune the electronic structure of SnS2 nanosheets, which showed effectively enhanced electrocatalytic activity and selectivity of CO2 reduction to formate and syngas (CO and H2). The oxygen-injection SnS2 nanosheets exhibit a remarkable Faradaic efficiency of 91.6% for carbonaceous products with a current density of 24.1 mA cm−2 at −0.9 V vs RHE, including 83.2% for formate production and 16.5% for syngas with the CO/H2 ratio of 1:1. By operando X-ray absorption spectroscopy, we unravel the in situ surface oxygen doping into the matrix during reaction, thereby optimizing the Sn local electronic states. Operando synchrotron radiation infrared spectroscopy along with theoretical calculations further reveals that the surface oxygen doping facilitated the CO2 activation and enhanced the affinity for HCOO* species. This result demonstrates the potential strategy of surface oxygen injection for the rational design of advanced catalysts for CO2 electroreduction. Highlights: 1 A surface oxygen-injection strategy is proposed to synergistically modulate the electronic structure of the SnS2 nanosheets, thereby regulating the oxophilicity of the catalyst surface. 2 The surface oxygen doping facilitates the CO2 activation and enhances the affinity for HCOO* species. 3 The oxygen-injection SnS2 nanosheets exhibit a remarkable Faradaic efficiency of 91.6% for carbonaceous products with a current density of 24.1 mA cm−2 at -0.9 V vs RHE.